A Philosophy of Cover Songs. - Magnus, P. D. (Open Book Publishers, 2022)
Cover songs are a familiar feature of contemporary popular music. Musicians describe their own performances as covers, and audiences use the category to organize their listening and appreciation. However, until now philosophers have not had much to say about them. In A Philosophy of Cover Songs, P.D. Magnus demonstrates that philosophy provides a valuable toolbox for thinking about covers; in turn, the philosophy of cover songs illustrates some general points about philosophical method.